2021
DOI: 10.1021/acs.iecr.1c01946
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Thermally Stable Inhibitor Based on Furfuryl Alcohol for Mild Steel Corrosion in a 15% HCl Medium for Acidizing Application

Abstract: Although corrosion inhibitors are widely used as a practical method for inhibiting metal corrosion in a variety of industries, their efficiency decreases dramatically at high temperatures. We present a thorough experimental and theoretical investigation into the inhibitory power of a novel thermally stable corrosion inhibitor based on furfuryl alcohol (FACI). The opencircuit potential, linear polarization resistance, potentiodynamic polarization, and electrochemical impedance spectroscopy techniques were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…The values displayed for Etot show that the adsorption of molecules to the metal surface is thermodynamically favored. Low adsorption EAds, as observed in all compounds is associated with a strong adsorption of the inhibitor molecules on Fe(110) surface [36,37]. Fig.…”
Section: Monte Carlo Simulationmentioning
confidence: 57%
See 1 more Smart Citation
“…The values displayed for Etot show that the adsorption of molecules to the metal surface is thermodynamically favored. Low adsorption EAds, as observed in all compounds is associated with a strong adsorption of the inhibitor molecules on Fe(110) surface [36,37]. Fig.…”
Section: Monte Carlo Simulationmentioning
confidence: 57%
“…Compounds A1-6 and B1-6 were simulated using the Monte Carlo method to assess the adsorption and possible interactions between them and Fe(110) surface along the low-index miller facet [8,22,25]. Fe (110) plane was selected for its good stability and well-packed structure [27]. The molecules and Fe (110) were optimized using the Forcite module as earlier described [8,25].…”
Section: Monte Carlo Simulationmentioning
confidence: 99%
“…The Rp behavior pattern in the presence of PILs obtained by LPR is shown in Figure . It was found that as the inhibitor concentration ( C INH ) was increased the current density ( i ) vs overpotential (η) slopes diminished, which implies higher Rp and suggests that the inhibition process on the steel surface occurred through the adsorption of PIL molecules. , This effect is also shown in Figure from the PDP behavior with respect to log i and C INH . The decrease of log i with C INH indicates that the PILs worked as CIs, yielding values below 175 ppm of poly­[VIMC4]­[Im], poly­[VIMC2]­[Br], and poly­[VIMC4]­[Br].…”
Section: Results and Discussionmentioning
confidence: 84%
“…As shown in Table , the anodic and cathodic Tafel slopes (β a and β c ) change with inhibitor concentration, implying that the inhibitor affects both the cathodic and anodic reactions. For both DTZA and DPZA, the deviation in corrosion potential E corr lies below 85 mV, and the corrosion inhibitors can be classified as mixed-type. , As the concentration of DTZA increases from 0.05 to 0.15%, the I corr value of N80 steel in lactic acid decreases from 116.5 to 42.55 μA/cm 2 , the corresponding polarization resistance R p increases from 74.67 to 157.11 Ω, and the inhibition efficiency IE increases from 74 to 90.7%. This finding suggests that both the anodic and cathodic reactions have been suppressed.…”
Section: Resultsmentioning
confidence: 99%
“…For both DTZA and DPZA, the deviation in corrosion potential E corr lies below 85 mV, and the corrosion inhibitors can be classified as mixed-type. 43,44 As the concentration of DTZA increases from 0.05 to 0.15%, the I corr value of N80 steel in…”
Section: Potentiodynamic Polarizationmentioning
confidence: 99%